Addressing physician shortages in Canada: The significance of adjusting population aging and changing hours of work by physicians. - Rabiul, Islam; Kralj, Boris; Sweetman, Arthur (My University, 2023)
Previous studies on physician shortages in Canada have predominantly focused on headcounts, billing systems, and burnout, disregarding the aspect of work hours due to data limitations. Unlike previous studies examining labor supply, our study utilizes up-to-date data spanning from 1987 to 2020 and adjusts for the significant impact of population aging and changes in physician work hours. Using the Labour Force Survey to incorporate these factors, we reveal notable shifts in expected medical services per person. This investigation offers valuable insights for medical professionals, the public, and governments when discussing and planning the optimal number of new physicians entering the field.
Keywords: Health; Labour; Statistical methods